Migration and climate change - Guchteneire, P. F. A. de [ (Paul F. A.)]; Pâecoud, Antoine , 1974-; Piguet, Etienne (Cambridge University Press, 2011)
"Migration and Climate Change provides the first authoritative overview of the relationship between climate change and migration, bringing together both case studies and syntheses from different parts of the world. It discusses policy responses, normative issues and critical perspectives from the point of view of human rights, international law, political science, and ethics, and addresses the concepts, notions and methods most suited to confronting this complex issue. The book constitutes a unique and thorough introduction to one of the most discussed but least understood consequences of climate change and brings together experts from a multitude of disciplines such as geography, anthropology and law, providing a valuable synthesis of research and debate"--Provided by publisher.